Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1440-169x.1997.t01-3-00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine forebrain and midbrain crest cells generate different characteristic derivatives in vitro

Abstract: Neural crest (NC) is a transient structure that gives rise to various types of tissues. Many NC cells are pluripotent in the sense that their progeny can generate more than one derivative. However, the potentiality to differentiate into certain derivatives, such as cartilage and bone, seems to be specified with respect to the neuraxial levels at which the NC generates. In order to compare the differentiation potentiality of different regions of head NC, the derivatives of forebrain and midbrain mouse NC have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…For example, works from Patrick Tam's lab [62,63] and Osumi-Yamashita's lab [64-67] clearly showed that DiI lineage tracing could be used effectively in mouse embryos in combination with whole embryo culture to study mammalian NCC development. Our labeling method utilizes a Cre-loxP/EGFP reporter system, in which labeling is both constant and continuous.…”
Section: Resultsmentioning
confidence: 99%
“…For example, works from Patrick Tam's lab [62,63] and Osumi-Yamashita's lab [64-67] clearly showed that DiI lineage tracing could be used effectively in mouse embryos in combination with whole embryo culture to study mammalian NCC development. Our labeling method utilizes a Cre-loxP/EGFP reporter system, in which labeling is both constant and continuous.…”
Section: Resultsmentioning
confidence: 99%
“…We examined these possibilities using cranial neural tube explants from T14 embryos (Chareonvit et al 1997). Explants devoid of surface ectoderm were cultured for 12 hours and cells that migrated from the explant were recovered and quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse primary cranial neural crest culture technique has been reported previously (Chareonvit et al, 1997). Midbrain and anterior hindbrain regions were identified by anatomic landmarks and microdissected from E8 Swiss Webster mouse embryos with four to six somite pairs.…”
Section: Methodsmentioning
confidence: 99%